Annual editions : marketing 00/01 - Richardson, John E. (Guilford, Conn. : Dushkin/McGraw-Hill, 2000)
This reader of public press articles concerns the marketing issues of the 1990s and beyond. It focuses on research, markets and consumer behaviour, developing and implementing marketing strategies, and global marketing.
Include Index.
Keywords: Marketing -- Handbooks, manuals, etc